A SYSTEMATIC REVIEW PROCESS TO EVALUATE SUICIDE PREVENTION PROGRAMS: A SAMPLE CASE OF COMMUNITY‐BASED PROGRAMS. Issue 1 (13th December 2012) - York, Janet; Lamis, Dorian A.; Friedman, Lee; Berman, Alan L.; Joiner, Thomas E.; Mcintosh, John L.; Silverman, Morton M.; Konick, Lisa; Gutierrez, Peter M.; Pearson, Jane
<x xml:space="preserve">Abstract</x> The Guide to Community Preventive Services (Guide), one of the most rigorous methods of systematic reviews, was adopted to evaluate the effectiveness of 16 community, primarily youth, suicide prevention interventions, through a multisectoral collaboration. The Guide steps for obtaining and evaluating evidence on effectiveness include: forming a multidisciplinary team; developing a conceptual approach to organizing, grouping, selecting, and evaluating the interventions; selecting the interventions; searching for and retrieving evidence; assessing the quality of and summarizing the body of evidence; translating the evidence of effectiveness into recommendations; considering additional evidence; and identifying and summarizing research gaps. The intervention effects were calculated using Hedge's g‐type (standardized mean differences) effect sizes. The strength of the body of evidence was characterized on the basis of suitability of the study design for assessing effectiveness and quality of study execution. Results indicated that student curriculum, combined curriculum and gatekeeper training, and competence programs have a positive effect on adolescent's knowledge and attitudes about suicide, but only a negligible effect on suicidal behaviors. Five of 7 studies with moderate to large effect sizes on outcomes were also those with both good quality of execution and the greatest suitability of the design. Policy recommendations are offered for the improved evaluation of the effectiveness of suicide prevention programs in youth.